RANCANG BANGUN SISTEM PEREKRUTAN KARYAWAN BERBASIS NODE.JS DI KOTA BATAM - Manurung, Edward Suranta Manurung; Ani Arnomo, Sasa (LPPM Universitas Putera Batam, 2024)
The problems faced in the form of conventional-based labor recruitment problems, of course this has shortcomings, such as the company having difficulty getting workers who meet the company's standard qualifications and data management for admins in storing job applicant data is still not neat. This research aims to describe the current system, analyze the current workforce recruitment system, and propose a solution in the form of a new web-based workforce recruitment information system that utilizes Unfield Modeling Language (UML), a programming language that combines PHP and MySQL as the database. The System Development Life Cycle (SDLC) method was used to build this application. This method consists of five stages: planning, analysis, design, implementation, and use. In particular, the Rapid Application Development (RAD) Software Development Method is an incremental software development process model that is well suited to short processing periods. The results of this research are in the form of a website and process flow diagrams created using use case diagrams, sequence diagrams, activity diagrams and class diagrams.